1984
DOI: 10.1128/jvi.51.3.760-767.1984
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody to simian virus 40 small t

Abstract: A monoclonal antibody, PAb280, was produced that recognizes simian virus 40 (SV40) small t but does not react with SV40 large T. The specificity of the antibody was analyzed by immunoprecipitation of labeled cell extracts, Western blotting, and immunocytochemistry. Small t was found to accumulate late in the SV40 lytic cycle and was localized in both the cytoplasm and the nucleus of cells infected with wild-type SV40. Importantly, antibodies against determinants common to SV40 large T and small t did not appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 30 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…1. Comparative single-cell analyses of pMEFd17 and 3T3 cells, abortively infected with SV40, for the expression of small t by using immunofluorescence staining of the cells with the smallt-specific monoclonal antibody PAb280 (33) indeed revealed that virtually all SV40-infected pMEFd17 cells displayed small-t staining (Fig. 5A), whereas only few (approximately 0.1%) of the infected 3T3 cells could be stained for small t (Fig.…”
Section: Fig 4 Correlation Between Sv40 Small-t Expression and Metamentioning
confidence: 98%
“…1. Comparative single-cell analyses of pMEFd17 and 3T3 cells, abortively infected with SV40, for the expression of small t by using immunofluorescence staining of the cells with the smallt-specific monoclonal antibody PAb280 (33) indeed revealed that virtually all SV40-infected pMEFd17 cells displayed small-t staining (Fig. 5A), whereas only few (approximately 0.1%) of the infected 3T3 cells could be stained for small t (Fig.…”
Section: Fig 4 Correlation Between Sv40 Small-t Expression and Metamentioning
confidence: 98%
“…SV40-transformed REF52 rat fibroblast cells (SV52) were metabolically labeled either with [ 35 S]methi-onine-[ 35 S]cysteine for 1 h or with 32 P i for 3 h, as described in Materials and Methods. Aliquots of whole-cell extracts from these cells were immunoprecipitated with monoclonal antibody PAb419, recognizing an N-terminal epitope of LT (53), to obtain total (i.e., free and complexed) LT, or with PAb421, recognizing a C-terminal epitope of p53 (42), to specifically precipitate LT complexed to p53. To purify uncomplexed (free) LT, these extracts were cleared of p53-LT complexes by three sequential immunoprecipitations with the p53-specific PAb421, and free LT was immunoprecipitated from the cleared extracts with PAb419.…”
Section: Free Lt and P53-complexed Lt Differ In Their Phosphorylationmentioning
confidence: 99%
“…The aim of these experiments was to determine whether PC-polymer-coated plates 1) support hybridoma cell viability, and 2) improve or maintain measurable antibody secretion when compared to well-known name brands of coated/surface-treated plates. The hybridoma cell lines used for these experiments were: PAb421, which produces an antibody able to recognize murine and human p53 at amino acid positions 363-372 (Harlow et al, 1981); PAb1801, which produces an antibody specific for human p53 and recognizes a denaturation-resistant epitope located at amino acid positions 32-79 (Banks et al, 1986); PAb246, which produces an antibody specific for murine p53 and recognizes amino acids at positions 86-107 (Yewdell et al, 1986); and PAb280, which produces an antibody specific for SV40 small t antigen and recognizes a denaturation-resistant epitope located at amino acid positions 83-114 (Montano and Lane, 1984). These cell lines were chosen because i) they express different amounts of very well-characterized monoclonal antibodies; thus, allowing the detection of antibody production across several ranges of magnitude; and ii) they originate from different independent cell fusions.…”
Section: Resultsmentioning
confidence: 99%
“…The hybridoma cell lines PAb421 (Harlow et al, 1981), PAb1801 (Banks et al, 1986), PAb246 (Yewdell et al, 1986), and PAb280 (Montano and Lane, 1984) were initially maintained in Dulbecco's Modified Eagle's Medium supplemented with 10% very low immunoglobulin containing fetal calf serum (FCS) (Gibco/Invitrogen, La Jolla, CA), containing 2 mM glutamine, 1 mM sodium pyruvate, and 100 U/ml penicillin/streptomycin (Gibco/Invitrogen). Cells were gradually weaned into hybridoma serum-free media (SFM Media, Gibco/Invitrogen) supplemented with 2 mM glutamine, 1 mM sodium pyruvate, and 100 U/ml penicillin/ streptomycin (Gibco/Invitrogen).…”
Section: Cell Culturementioning
confidence: 99%